We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
71
1
avatar

Find (f+g)(2) and (f-g)(3)

f(x)=3*8^x

g(x)=2*8^x+1

 Mar 25, 2019
 #1
avatar+101234 
0

( f + g) (2)   =  f(2) + g(2) =

 

[ 3*8^(2) ]  + [ 2*8^(2) + 1 ]   = [ 3 * 64 ] + [ 128 + 1 ]   =  [ 192 +  128 + 1 ] = 321

 

 

(f - g)  (3)  =  f(3) - g(3) =

 

[ 3*8^3 ]   - [ 2*8^3 + 1 ]  =  8^3 - 1  =    511

 

 

cool cool cool

 Mar 25, 2019

9 Online Users

avatar